Nano-Mechanical Analyses of Native and Cross-Linked Collagen I Matrices Reveal the Mechanical Complexity of Homogenous Samples - Le Cerf, Brock Alan; Pyne, Natasha Theresa; Kular, Jasreen; Boyle, Sarah Theresa; Beattie, David Allan; Krasowska, Marta; Samuel, Michael Susithiran (Frontiers in Physics, 2022)
While it is now well appreciated that the extra-cellular matrix (ECM) exerts biomechanical cues that direct critical cellular behavior, including cell proliferation, differentiation, migration, and survival, the molecular mechanisms underlying these cues remain mysterious. It has long been known that the ECM is also a source of biochemical cues that influence these processes, but the way these interact with ECM biomechanics also remains largely unknown. The systematic study of these relationships has been hampered by a paucity of models and the tools to interrogate them. Studies of complex models and tissue samples employing techniques such as atomic force microscopy (AFM) have informed much of our current understanding of how mechanical cues are transduced by the ECM and how cells respond to them. However, key observations made using such complex systems cannot be reliably assigned to the ECM or its components without a precise understanding of how these components respond to and exert mechanical force at the nanoscale – the scale at which individual cells respond. To address this knowledge gap, we used AFM to study the nanomechanical properties of a simple model, consisting only of type I collagen, the most abundant component of the ECM. Intriguingly, our data show bimodal distribution that is entirely attributable to type I collagen, greatly simplifying the interpretation of these studies. Furthermore, we examined the nanomechanical influence of tissue fixation by protein cross-linking, an approach commonly used in research and medical histopathology, revealing a significant and non-uniform distortion of the nanomechanical profile of fixed samples, that has the potential to introduce artifacts into the nanomechanical characterization of tissues. In contrast to the clear observation of mechanical differences induced by crosslinking, Fourier-transform infrared (FTIR) spectroscopy revealed only subtle alterations to the chemical signature of the collagen, highlighting the importance of nanomechanical approaches for the complete characterization of model systems and tissues.